Geopolitical atlas of the oceans : the law of the sea, issues of delimitation, maritime transport and security, international straits, seabed resources - Ortolland Didier; Lévy Jean-Pierre; Auzende Jean-Marie; Verret Thierry (Éditions TECHNIP, 2017)
This atlas endeavours to present the various components of present maritime geopolitics. This publication deals with the major issues relating to maritime spaces and their delimitations, navigation and security, international straits and seabed resources. As such, it should represent an essential tool for the understanding of States' ocean policies and governmental stances.
Keywords: Géopolitique Cartes; Droit maritime Cartes; Eaux territoriales Cartes; Droit de la mer Cartes; Ressources marines Cartes; Mer Cartes